Biofilm formation of Flavobacterium psychrophilum on various substrates. (9th October 2018) - Ríos‐Castillo, Abel G.; Thompson, Kim D.; Adams, Alexandra; Marín de Mateo, Mercedes; Rodríguez‐Jerez, José J.
Abstract: The ability of Flavobacterium psychrophilum to adhere to and form biofilms on different types of materials used on rainbow trout ( Oncorhynchus mykiss ) farms was evaluated in this study. F. psychrophilum NCIMB 1947 T, was inoculated onto a variety of different surfaces, including stainless steel, plastic, glass, wood, and zinc pyrithione encapsulated antibacterial plastic. The samples were then cultured in a humidified chamber or transferred into fish tanks containing either (1) freshwater or (2) filtered lake water. The formation of biofilms was quantified by fluorescent microscopy. F. psychrophilum formed biofilms on all of the surfaces tested; however, the adherence of the bacterium to the antibacterial plastic was much lower than the attachment observed on the other surfaces, illustrating the bacteriostatic properties of this material for F. psychrophilum . Moreover, bacterial numbers were greater on the surfaces maintained in lake water compared with those maintained in freshwater. The mineral composition of the lake water may have been responsible for the increased bacterial adherence observed between the two types of water. Treatment of the water, regular cleaning of equipment and the use of antimicrobial material to house the fish may help reduce biofilm formation by F. psychrophilum in fish farming systems.